Inter- and intra-rater reliability of handheld dynamometry for lower extremity strength testing in pre-professional dancers - Schaeffer, M.; Daniels Abbruzzese, L.; Tawa, Z.; Schultz, K.; Binney, J.; Boyle, J.; Bronner, S. (Journal of Dance Medicine & Science, 2021)
Handheld dynamometry (HHD) using external fixation has demonstrated high inter- and intra-rater reliability. Handheld dynamometry offers an objective way to quantify strength; however, setting up external stabilization devices for HHD can be time consuming. This study examined the reliability of HHD for lower extremity strength in dancers using body weight stabilization. Twenty-six pre-professional dancers (age: 20.64 ± 2.21 years) were recruited and assessed by three testers: an experienced physical therapist (ePT), a novice physical therapist (nPT), and a student physical therapist (SPT). To avoid testing fatigue, dancers were divided into two testing groups and were evaluated on separate weekends. Testers used HHD to test isometric force production of six muscle groups in the first cohort and seven different muscle groups in the second cohort. Testing positions were standardized and utilized a "make" test protocol. Intra-class correlation coefficients (ICC), 95% confidence interval, and standard error of measurement were calculatedfor each position. Inter-rater reliability was > 0.75 for all ICC measures except knee extension and ankle eversion. Intra-rater reliability was > 0.75 for all ICC measures except the ePT (tester A) day 2 for hip extension, internal rotation seated, knee extension, and ankle dorsiflexion; nPT (tester B) day 1 knee flexion; and SPT (tester C) for day 1 knee extension and ankle eversion and days 1 and 2 for ankle dorsiflexion and inversion. It is concluded that HHD can reliably measure force production of hip, knee, and ankle muscle groups without use of external fixation devices.